(untitled) (Journal of Hama University, 2024)
The eloquence of the scientific construction in the poetry of qais bin al-malouh. Research summary this research seeks to study the rhetorical meanings of the types of medical composition in the poetry of qais bin al-malouh and toreveal the aesthetic function that is based on the applied side of the compositional style, including the methods of calling, chanting, commanding, wishing, and forbidding, with the aim of reaching the depths of the human soul. The research concluded with scientific results that show the impact of metaphorical meanings and their significance for the poet.